2021
DOI: 10.1021/acs.joc.1c01194
|View full text |Cite
|
Sign up to set email alerts
|

[3 + 2 + 1] Pyridine Skeleton Synthesis Using Acetonitrile as C4N1 Units and Solvent

Abstract: The first [3 + 2 + 1] methodology for pyridine skeleton synthesis via cascade carbopalladation/cyclization of acetonitrile, arylboronic acids, and aldehydes was developed. This reaction proceeds via six step tandem reaction sequences involving the carbopalladation reaction of acetonitrile, a nucleophilic addition, a condensation, an intramolecular Michael addition, cyclization, and aromatization. Delightfully, both palladium acetate and supported palladium nanoparticles catalyzed this reaction with similar cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…A small amount of 4,4′-dimethyl-biphenyl was found as a byproduct both in those two reactions, which demonstrated that the transmetalation of the palladium catalyst and aryboronic acid occurred firstly. Based on the literature and our previous work ( Chen et al, 2013 ; Wang et al, 2013 ; Bai et al, 2021 ), the proposed mechanism of the present reaction is presented in Scheme 2 . The reaction began with transmetalation of the palladium catalyst and aryboronic acid to form intermediate A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A small amount of 4,4′-dimethyl-biphenyl was found as a byproduct both in those two reactions, which demonstrated that the transmetalation of the palladium catalyst and aryboronic acid occurred firstly. Based on the literature and our previous work ( Chen et al, 2013 ; Wang et al, 2013 ; Bai et al, 2021 ), the proposed mechanism of the present reaction is presented in Scheme 2 . The reaction began with transmetalation of the palladium catalyst and aryboronic acid to form intermediate A.…”
Section: Resultsmentioning
confidence: 99%
“…Following this pioneering work, a number of related works were reported, and a broad range of coupling partners could react with nitriles via intermolecular carbopalladation, such as potassium aryltrifluoroborates ( Chen et al, 2013 ; Wang et al, 2013 ), benzoic acid ( Lindh et al, 2010 ), heteroarene ( Jiang and Wang, 2013 ; Jiang and Wang, 2014 ), sodium arylsulfinates ( Liu et al, 2011 ; Skillinghaug et al, 2014 ), arylhydrazines ( Cheng et al, 2017 ), and arylsulfonyl hydrazides ( Meng et al, 2018 ) ( Scheme 1 ). Inspired by our previous work that supported PdNPs as suitable catalysts for pyridine synthesis via tandem carbopalladation/cyclization of acetonitrile, arylboronic acids, and aldehydes ( Bai et al, 2021 ), we recently questioned whether supported PdNPs could be an ideal alternative heterogeneous catalyst for the construction of ketone under mild condition. To the best of our knowledge, general methods for employing heterogeneous catalysts to synthesize ketone via carbopalladation of nitrile are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…On another note, Bai and coworkers discussed an interesting way to access [3 + 2 + 1] pyridine skeletons in one step ( Bai et al, 2021 ). Starting from vanillin, a cascade carbopalladation-cyclization is carried out in presence of phenylboronic acid, palladium acetate (catalyst), 6-methyl-2,2′-bipyridine (bidentate ligand), and 1-fluoro-2,4,6-trimethylpyridin-1-ium trifluoromethanesulfonate as the oxidant, affording compound 8 in 71% yield.…”
Section: Modification Of the Aldehyde Groupmentioning
confidence: 99%
“…31,32). Recently, pyridines have been synthesized from acetonitrile, arylboronic acid and aldehydes 33 via six-step tandem sequences involving the carbopalladation reaction of acetonitrile, a nucleophilic addition, condensation, an intramolecular Michael addition, cyclization, and aromatization. In addition, pyrrolyl-pyridines have been obtained via the reaction of an alkyne with a phosphonium cation in the presence of Tf 2 O and TfOH followed by treatment of the phosphorane-containing vinyl cation with acetonitrile.…”
Section: Introductionmentioning
confidence: 99%